Higher Education Divided National Expectations and the Bifurcation of Purpose and National Identity, 1946-2016 - Palmadessa, Allison L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This book critically considers how tertiary institutions of higher education in the United States are charged with the duty of preserving democracy, teaching citizenship literacy, and contributing to economic stability. The author offers a comparative analysis of how presidential and national policy agendas shape these social institutions$1 (Bre-creation and re-constitution of ideological identities that influence the social position of the participants in the institution types, creating a divide in the realization of national identity across institutional and class lines. In fulfilling this role, four- and two-year institutions become representations of the social class divisions in the United States as the institutions and their students experience American national identity differently. By answering a call to serve the American public and presidential agendas, institutions of higher education reinforce the economic and social divisions in American society, resulting in varied understandings of American national identity.s
1. Establishing National Identity and the Purpose of Higher Education in the United States -- 2. Preserving and Promoting Democracy: University Demands and the Importance of the Community College in Post-War America, 1946-1953 -- 3. Dualities and Challenges: Higher Education in the Heart of the Cold War, 1953-1969 -- 4. Servicing the Public and the Marketplace for National Growth, 1970-1989 -- 5. Capital Gains and Higher Education: The Entrepreneurial University and the Community College as a Facilitator of American Social Mobility in the 1990s -- 6. Human Capital and Market Commodities: Higher Education's Role in the 21st Century -- 7. Higher Education in the Era of Trump: Considering the Ambiguous Future of Tertiary Higher Education in "New American Moment".
Keywords: Educational policy; Education and state; Higher education; School management and organization; School administration; Education$1 (BHistory.s; Educational Policy and Politics; Higher Education; Administration, Organization and Leadership; History of Education